Gut Microbiome, Neuroinflammation, and Fetal Alcohol Spectrum Disorders: Insights from Rodent Models - Abdulrahman M. Busayli; Wenhua Xu; Ghaidaa A. Raffah; Gang Chen (Biology)
Fetal alcohol spectrum disorder (FASD) is a significant public health issue that affects children. It results from ethanol exposure during pregnancy, leading to considerable physical, neurodevelopmental, behavioral, and cognitive deficits. The exact mechanism is not well understood. Recently, considerable attention has been focused on the influence of gut microbiome on brain development through the gut–brain axis. Changes in the gut microbiome resulting from ethanol exposure may contribute to the pathology of FASD, potentially involving neuroinflammation. This literature review summarizes the existing research and primary animal studies on the impact of early ethanol exposure on the gut microbiome, neuroinflammation, brain development, and behavioral consequences. The evidence suggests that early ethanol exposure alters the gut microbiome, which may induce neuroinflammation, brain damage, and cognitive impairment. However, a clear causal relationship among these factors remains to be fully elucidated.